2022
DOI: 10.1186/s12967-022-03346-2
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and altered endothelial biomarkers in patients with post-COVID-19 syndrome and chronic fatigue syndrome (ME/CFS)

Abstract: Background Fatigue, exertion intolerance and post-exertional malaise are among the most frequent symptoms of Post-COVID Syndrome (PCS), with a subset of patients fulfilling criteria for Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). As SARS-CoV-2 infects endothelial cells, causing endotheliitis and damaging the endothelium, we investigated endothelial dysfunction (ED) and endothelial biomarkers in patients with PCS. Methods We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(176 citation statements)
references
References 53 publications
9
136
3
Order By: Relevance
“…A first finding of our study was that the prevalence of post-COVID-19 fatigue (70%) was similar between the three SARS-CoV-2 variants suggesting that COVID-19 is associated with long-lasting post-fatigue, sharing common symptoms with myalgic encephalomyelitis/chronic fatigue syndrome [23]. In fact, similar endothelial dysfunction has been found in patients with post-COVID-19 symptoms and those with myalgic encephalomyelitis/chronic fatigue syndrome [24]. It could be hypothesized that although some differences (e.g., higher viral load, higher transmissibility, potential reinfections) between SARS-CoV-2 variants have been identified, the pathogenic cell-to-cell mechanisms associated with the development of post-COVID-19 fatigue may be similar between all variants.…”
Section: Discussionsupporting
confidence: 72%
“…A first finding of our study was that the prevalence of post-COVID-19 fatigue (70%) was similar between the three SARS-CoV-2 variants suggesting that COVID-19 is associated with long-lasting post-fatigue, sharing common symptoms with myalgic encephalomyelitis/chronic fatigue syndrome [23]. In fact, similar endothelial dysfunction has been found in patients with post-COVID-19 symptoms and those with myalgic encephalomyelitis/chronic fatigue syndrome [24]. It could be hypothesized that although some differences (e.g., higher viral load, higher transmissibility, potential reinfections) between SARS-CoV-2 variants have been identified, the pathogenic cell-to-cell mechanisms associated with the development of post-COVID-19 fatigue may be similar between all variants.…”
Section: Discussionsupporting
confidence: 72%
“…However, such impaired diffusion could also be explained by direct damage to the endothelium (40) leading to exercise intolerance as observed in chronic fatigue syndrome (41). Similarly, endothelial dysfunction has been reported in PASC with and without chronic fatigue syndrome (42). Interestingly, all the aforementioned factors may be linked to autonomic dysregulation (43,44).…”
Section: Discussionmentioning
confidence: 98%
“…An investigation of autopsy samples demonstrated viral persistence, resulting in multiple organ injury and various clinical presentations [ 107 ]. The role of inflammatory biomarkers in its pathogenesis is discordant since some studies have observed a persistently elevated biomarkers [ 103 , 108 , 109 ], while some researchers also show there is no direct correlations between them [ 110 ].…”
Section: Discussionmentioning
confidence: 99%